Effects of radiation on free convection from a heated horizontal circular cylinder in the presence of heat generation - N. Zainuddin; I. Hashim; H. Saleh; R. Roslan (Universiti Kebangsaan Malaysia, 2016)
Effects of radiation on free convection about a heated horizontal circular cylinder in the presence of heat generation are investigated numerically. The cylinder is fixed and immersed in a stationary fluid, in which the temperature is uniformly heated about the temperature of the surrounding fluid. The governing equations are transformed into dimensionless non-linear partial differential equations and solved by employing a finite difference method. An implicit finite difference scheme of Crank Nicolson method is used to analyze the results. This study determined the effects of radiation parameter, Rd heat generation parameter, γ and the Prandtl number, Pr on the temperature and velocity profiles. The results of the local heat transfer and skin-friction coefficient in the presence of radiation for some selected values of Pr and γ are shown graphically.